Getting the Message : A History of Communications - Laszlo Solymar
The past century has seen developments in communications technology that rival those in any other field of human activity. Significant advances are made every year, and the impact on our day-to-day lives has been tremendous. Getting the message explores the fascinating history of communications, starting with ancient civilizations, the Greeks and Romans, then leading through the development of the electric telegraph, and up to the present day with e-mail and cellular phones. In clear, non-technical language the book explains the details of each new development while interweaving ideas from politics, economics, and cultural history. The book concludes with a look at the possible future developments and how they may further transform how we live. Lavishly illustrated and including many original illustrations, the book is an informative and highly entertaining guide to this lively field.